RELATION OF COAL FREEZING ADHESIVE STRENGTH WITH WATER-LUBRICATING COEFFICIENT OF KINETIC FRICTION - WANG ChunHua; XU HanWen; HAO ZhiYong; QU Hui; WANG ZhongXian (Jixie qiangdu)
Coal is the important basic energy in China,however due to the problems of conveyor belt running deviation and avultion caused by freezing adhesive turnabout roller surface,it seriously restricts with coal mine safe and efficient production in cold regions during winter and brings huge economic losses to the company,although existing solutions have a certain ease of coal freezing adhesion but can not fundamentally solve the problem. Through the freezing adhesive strength test device designed by ourselves,under conditions of- 25℃ temperature and 3h freezing time,freezing adhesive characteristic of four different materials with moisture content 40% of the coal slime were tested. Experimental studies have found that with the decrease of material waterlubricating coefficient of kinetic friction coal normal and tangential freezing adhesive strength decrease,it shows a certain linear relation,the results indicate that improving the water-lubricating performance can reduce the freezing adhesive strength,the discovery has important guiding significance to the selection and preparation of anti-freezing adhesive coating in engineering field,it deserves further explore and study.